S1 family selection in early maturing maize populations in Striga infested and Striga free environments - Badu-Apraku, Baffour; Fakorede, M.A.B.; Lum, A.F. (Wiley, 2008)
Striga and drought are major constraints to maize (Zea mays L.) production in the savannas of west and central Africa (WCA). A study was conducted in 2005 and 2006 in Nigeria to determine the level of resistance to Striga hermonthica for two early-maturing maize populations, one white and one yellow, and to assess the progress made in improving each for grain yield and level of resistance after four cycles of S1 recurrent selection. Percentage yield gain per cycle of the yellow population when Striga infested was 13% with r2 = 82% and 5% with r2 = 97% in a Striga-free environment. Corresponding values for the white population were 15% with r2 = 40% and 1% with r2 = 9% for the two Striga environments. For the two populations, therefore, realized gain in grain yield was higher under Striga-infested than Striga-free conditions. Yield gains in the advanced cycles of selection were accompanied by increased number of ears per plant in both populations. Striga damage at 10 wk after planting (WAP) and Striga emergence at 8 WAP decreased by about 5 and 4% cycle–1, respectively in the yellow population. For the white population, Striga damage decreased also by about 5 and 4% per cycle–1 at 8 and 10 WAP, respectively, while Striga emergence decreased by about 5% cycle–1 at 8 WAP. In conclusion, S1 recurrent selection was effective in improving grain yield and Striga resistance in the two early maize populations.